Financing social protection - Koutsampelas, Christos; Kammas, Pantelis; Andreou, Sofia N. (My University, 2019)
The social protection system of Cyprus consists of a comprehensive range of contributory and non-contributory benefits. The social protection system is constantly changing and adapting, and its architecture combines elements from a variety of welfare models. About 19.1% of GDP was devoted to social protection in 2016. This is well below the EU-28 level. And yet, the trend is upward: between 2005 and 2016, the share of expenditure on social protection in GDP increased by 2.5 percentage points (pp). The increase in the relative and real level of social protection spending is mostly driven by pensions, as a result of population ageing and the gradual ‘maturation’ of the pension system (an increasing number of pensioners with richer contribution records have entered the pension system in the last decade). As a result, the share of old-age benefits in total spending has increased – and will most probably increase further over the next decades due to demographic factors. On the other hand, the share of healthcare spending in total spending has decreased, bucking European trends. The underfunding of the healthcare system is a persistent problem in Cyprus, mostly due to procrastination in reforming the system. There has also been an increase in the share of means-tested benefits, which may be attributable to the adaptation of the welfare state to recent economic swings, as well as to the political attractiveness of targeted instruments. In terms of financing structure, social protection in Cyprus has many similarities to what pertains in the rest of the EU; but there are also differences. The system is financed 50% by government revenues and 45.3% by social contributions; half of those social contributions are paid by employers, and the other half paid by employees and self-employed persons. The share of general government revenues in total financing increased by 4 pp between 2005 and 2015, and the share of the category ‘other receipts’ decreased. Meanwhile more weight is gradually being placed on financing the system through social contributions. This latter trend is in contrast to the EU-28, where the share of contributions in total financing is declining in the majority of countries. Interestingly, a number of ongoing and planned reforms point to further increases in the share of social contributions in the total financing mix. Specifically, social insurance contributions (financing old-age benefits and other contributory benefits) have increased in 2019, and further increases are planned over the next decades. The new National Healthcare System, which is expected to be fully operational by 2020, will be financed by contributions levied on labour earnings, income from self-employment and pensions (the state will contribute, too). Breaking general government revenues down into their major constituent parts, it may be observed not only that the share of social contributions and general government revenues has increased, but also that the increases in government revenues have come mostly from: (i) increased VAT tax revenues and (ii) corporate income tax revenues. Personal income tax revenues remained relatively stable during the period under investigation. This financing mix presents some important advantages (lower risk of evasion, low collection and administrative costs and less distortion of work incentives). However, it must also be stressed that the increased reliance on social contributions in recent years (which is expected to continue in the future) makes the financing of the social protection system vulnerable to demographic ageing. This is a threat that should be addressed effectively in the near future. Moreover, policy makers should turn the spotlight on labour market conditions and institutions in Cyprus, and design appropriate reforms to mitigate the impact of increasing social contributions on labour costs.